2016
DOI: 10.1016/j.microrel.2015.12.031
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of thermo-mechanical reliability of solder joints in crystalline silicon solar cell assembly

Abstract: A robust solder joint in crystalline silicon solar cell assembly is necessary to ensure its thermo-mechanical reliability. The solder joint formed using optimal parameter setting accumulates minimal creep strain energy density which leads to longer fatigue life. In this study, thermo-mechanical reliability of solder joint in crystalline silicon solar cell assembly is evaluated using finite element modelling (FEM) and Taguchi method. Geometric models of the crystalline silicon solar cell assembly are built and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(14 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…For this purpose, some approaches and submodels along with the experimental procedures have been proposed to assess the lifetime of the electronic packages under both thermal cycling and vibration loading. [3][4][5][6][7] The primary results indicated that solder joints are the most susceptible parts of the electronic assembly under either thermal or mechanical loadings. [8][9][10] For instance, Zhang et al 11 showed that the maximum inelastic energy is accumulated on the solder balls in the bottom of fine-pitch ball grid array structure.…”
Section: Introductionmentioning
confidence: 99%
“…For this purpose, some approaches and submodels along with the experimental procedures have been proposed to assess the lifetime of the electronic packages under both thermal cycling and vibration loading. [3][4][5][6][7] The primary results indicated that solder joints are the most susceptible parts of the electronic assembly under either thermal or mechanical loadings. [8][9][10] For instance, Zhang et al 11 showed that the maximum inelastic energy is accumulated on the solder balls in the bottom of fine-pitch ball grid array structure.…”
Section: Introductionmentioning
confidence: 99%
“…Thanks to the publicity available resources 5,[39][40][41][42][43][44][45] , we also created a huge number of input data to enrich the data resource needed to train the proposed model. It is worth-mentioning that all the collected data are extracted from the finite element model (FEM) simulation outcomes.…”
Section: Proposed Methodologymentioning
confidence: 99%
“…Such electro-thermomechanical stresses will cause considerable inelastic strain in the solder joint as the weak component in the power modules (Samavatian et al , 2018a). Inelactic strain has been said to be a perfect failure indicator in the lifetime analysis using FEM simulations (Zarmai et al , 2016; Kavithaa et al ,2020). Hither, inelastic strain will play the role of failure indicator during FEM simulations.…”
Section: Finite Element Modelingmentioning
confidence: 99%